2015
DOI: 10.2147/ov.s66091
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic virotherapy for human malignant mesothelioma: recent advances

Abstract: Cancer virotherapy is an attractive alternative to conventional treatments because it offers a wide range of antitumor effects due to 1) the diversity of the oncolytic viruses that are now available and 2) their multifaceted activities against both tumor cells and tumor vessels, in addition to their ability to induce antitumor immune responses. In this review, we summarize preclinical and clinical data regarding the targeting of malignant mesothelioma (MM) by oncolytic viruses. We also discuss the potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Although OVs are potentially powerful therapeutic agents against cancer, they frequently prove to be more effective in combinatorial treatments and are often tested in combination with standard chemotherapeutic agents [19,22,55]. In the present study, we observed that CpHV-1 strongly synergized with cisplatin, and this agent combination exerted no toxic effect on mesothelial cells.…”
Section: Discussionsupporting
confidence: 47%
“…Although OVs are potentially powerful therapeutic agents against cancer, they frequently prove to be more effective in combinatorial treatments and are often tested in combination with standard chemotherapeutic agents [19,22,55]. In the present study, we observed that CpHV-1 strongly synergized with cisplatin, and this agent combination exerted no toxic effect on mesothelial cells.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, investigating how to induce potent antitumor immune responses is essential for enhancing the therapeutic efficacy of virotherapy in patients. 3,45 Most of the viruses that are currently being tested in clinical trials were designed to acquire the capability to trigger immune responses. 4,5,41,42 To this end, understanding the mechanism underlying the blockade and regulation of systemic antitumor immunity is critical for the further improvement of oncolytic virotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Notably CD46 is selectively expressed in malignant cells and not in inflammatory mesothelium, thus allowing for a highly specific delivery [ 138 ]. Overall combinations of oncolytic viruses with other types of cancer treatments results in synergistic effects [ 139 ]. Virotherapy, in combination with immunotherapy in particular, has shown promising results in MPM.…”
Section: Cutting-edge Molecularly Oriented Therapiesmentioning
confidence: 99%